Abordagem para diagnóstico de problemas em aplicações de E-GOV - um retrato dos municípios brasileiros. - Bittar, Thiago Jabur (Universidade Federal de São Carlos, 2006)
In this work, the main theme is to collect data to diagnose problems and formalize solutions in the Brazilian municipal Electronic Government (E-GOV) domain, focusing on G2C (Government to Citizen) at the first moment. In order to do that, this research analyses and relates: the main problems and challenges to promote E-GOV in general terms and in Brazilian cities as well as in cities from all over the world; the Legislation and guidelines of E-GOV project. So, it was developed a methodological approach composed by a group of methods and complementary macro-activities to scale the results understanding up, supporting the building and spreading of a significant, valid and widespread knowledge in this domain. Such macro-activities used to gather the data are: (i) investigating cities information automatically, (ii) contacting the Administrations via a marketing research and (iii) evaluating the sites by inspection in order to validate the diagnosis. Thus, once the problem recurrence is verified and a successful solution is observed, a propitious base of information is configured so that Proto-Patterns can be identified and formalized as a structured and elegant way to document and diffuse the solutions in the context of E-GOV development to cities, relating to the Software Engineering (SE) and Human-Computer Interaction (HCI) domains.
Approach for Problems Diagnosis in E-GOV Applications - a portrait of the Brazilian cities
Keywords: Engenharia de software; Governo eletrônico; World Wide Web (Sistema de recuperação da informação); Municípios; Interação homem-máquina; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::ENGENHARIA DE SOFTWARE